The effects of spaced versus massed extinction training on extinction retention of conditioned fear learning in male rats - LeVasseur, Grant W.; Cilley, Timothy; Szewczuk, Michelle; Perrine, Shane A.; Norrholm, Seth D. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionExtinction learning of conditioned fear behavior has been used as a translational model to study human fear-, anxiety-, trauma-, and stressor-related disorders and their underlying neurobiology in animal models because the underlying neural processes of extinction learning are fundamental to the most effective clinical interventions for these disorders. Specifically, extinction-based prolonged exposure therapy is the first-line, gold-standard, cognitive behavioral treatment for fear-, trauma-, stressor-, and anxiety-based disorders. However, the ways that parametric differences in methodologies alter extinction learning are still not well understood.MethodsTherefore, in the current study, we altered the number of days on which an equal number of extinction trials were presented in an extinction of conditioned fear learning-paradigm. As part of this paradigm, we employed fear-potentiated startle as a primary outcome measure of fear responses in adult, male rats. One group received 120 massed extinction trials in 1 day, a second group received 120 extinction trials across 2 days, and a final group received 120 extinction trials spaced across 4 days. We hypothesized that a greater number of days of extinction training would lead to improved extinction retention.ResultsWe found minimal differences between groups on the final test of extinction retention, although increased fear behaviors were observed at the start of the second day of extinction training in the 2-day group.DiscussionThese findings have implications with respect to the flexibility of fear extinction methodologies employed as well as to how data generated from chosen paradigms is interpreted.